2001
DOI: 10.1007/s11661-001-0259-7
|View full text |Cite
|
Sign up to set email alerts
|

Forming-limit diagrams of aluminum tailor-welded blank weld material

Abstract: The current work develops forming-limit diagrams (FLDs) for weld materials in aluminum tailorwelded blanks (TWBs) under biaxial stretching conditions. Aluminum TWBs consist of multiplethickness and alloy sheet materials welded together into a single, variable-thickness blank. The manufacture of TWBs and their application in automotive body panels requires their constituent weld material to deform under biaxial loading during sheet-metal stamping. The weld geometry is typically nonuniform and relatively small, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…These thin-walled structures have the same wall thickness, but their inherent weakness is that they are not able to make full use of the material to meet the requirements for lighter weight. 5 Therefore, it is widely considered that a new structure with varying thicknesses should be used to improve material usage. Tailor rolling blanks (TRBs), which lead to a continuous thickness variation in a workpiece, have been developed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…These thin-walled structures have the same wall thickness, but their inherent weakness is that they are not able to make full use of the material to meet the requirements for lighter weight. 5 Therefore, it is widely considered that a new structure with varying thicknesses should be used to improve material usage. Tailor rolling blanks (TRBs), which lead to a continuous thickness variation in a workpiece, have been developed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have concentrated on the mechanical properties of TWBs [3], the movement of weld line [4], forming process design [5], finite element simulation [6], forming limit (formability) [7] and failure prediction for TWBs [8]. Generally, the overall formability of TWBs is significantly affected by the welding parameters [9], especially for heat-treatable aluminium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Further, negative strain rate sensitivity was observed at all strain rates. Davies et al [10] reported their work in developing theoretical forming limit diagrams (FLDs) for weld materials. They used power law along with the Hosford yield criteria to obtain right-hand-side of FLD.…”
Section: Introductionmentioning
confidence: 99%